Evaluation of the Impact and Satisfaction of Creating a Mother–Child Educational Podcast by University Nursing Students - Sergio Martínez-Vázquez; Rocío Adriana Peinado-Molina; María Antonia Díaz-Ogállar; Antonio Hernández-Martínez; Juan Miguel Martínez-Galiano (Nursing Reports, 2026)
Aim: To evaluate the effect of a student-generated podcast intervention focused on maternal–child health topics on nursing students’ self-perceived knowledge, educational satisfaction, and gameful engagement. Introduction: Health education is essential for promoting healthy lifestyles and preventing disease, making the acquisition of effective communication skills vital for nursing undergraduates. While digital audio media and podcasts are increasingly popular pedagogical tools, traditional applications rely on passive listening. Student-generated podcast production represents an active learning approach that may enhance engagement, communication skills, and content synthesis. Design: Quasi-experimental study without randomization. Methods: The intervention was conducted across a 4-week framework comprising 8 contact hours of faculty guidance alongside independent teamwork. First-year nursing students organized into small collaborative groups (3–4 peers) received initial training on digital audio pedagogy, metadata, and production. Teams developed 5-to-7-min podcast capsules addressing eight evidence-based maternal–child health themes. Faculty provided structured formative checkpoints for script clinical validation and technical audio editing guidance. All completed podcasts were evaluated using a 100-point rubric assessing scientific accuracy (35%), communication clarity (25%), narrative engagement (20%), and technical quality (20%); thirty top-scoring episodes were selected for public radio broadcasting. Pre-and post-intervention self-administered questionnaires measured self-perceived knowledge across all eight topics, educational satisfaction, and gameful experience via the validated 27-item Gameful Experience Scale (GAMEX). Results: A total of 130 valid questionnaires were analysed at each assessment point. Self-perceived knowledge was higher at the post-intervention assessment across all eight topics (all Holm-adjusted p < 0.001). After Holm correction, general podcast satisfaction (adjusted p = 0.036), fulfilment of expectations (adjusted p = 0.036), recommendation to friends or family (adjusted p < 0.001), perceived importance of podcasting for maternal health (adjusted p = 0.036), and perceived ease of setting up a podcast (adjusted p = 0.005) remained statistically significant. Creative Thinking, Mastery, and the overall GAMEX score were nominally higher before multiplicity adjustment, but none remained statistically significant after Holm correction (adjusted p = 0.126, 0.234, and 0.158, respectively). Conclusions: Student-generated podcasting was associated with higher self-perceived knowledge and favourable appraisal on several educational outcomes. GAMEX differences were exploratory after Holm correction.